Meaning of “Pakan” symbols in the ritual of Penan Community in Ulu JelalongTubau, Bintulu Sarawak - Keti, Sarina; Magiman, Mohamad Maulana; Mohd. Yusof, Haji Ahmad; Abdullah, Azlina (Human Resources Management Academic Research Society (HRMARS), 2024)
Beliefs are intended as a behavioral guideline for the entire community of those who understand and believe in any particular belief. The Penans, especially those who reside in the Ulu Jelalong Tubau, Bintulu area have an important belief in bringing their community together. Thus, this research is conducted to study “The Pakan Symbol in the Ritual of the Penan Community of Ulu Jelalong, Bintulu, Sarawak”. Its main focus is to study the roles of symbols available during the Pakan ceremony, which are also applied in every ritual related to the culture of the Penan people at Ulu Jelalong Tubau, Bintulu area. This Pakan culture has indirectly introduced the identity of the Penan people themselves where the superiority of the people derives from its cultural values as it reflects their uniqueness and privilege. The three main objectives of this research are, to study the feed ritual processes in the Penan Saoh community in Kampung Julaihi Keti, Ulu Jelalong, Bintulu Sarawak. Second, identify the types of symbols in the ritual feed in the culture of the community Penan Saoh, and third analyze the meaning of symbols in the feed ritual in the culture of the Penan Saoh people. As a result, efforts were made to focus on the Pakan culture which became a symbol of the Penan community rituals at Ulu Jelalong area. Pakan is a spirit-feeding ceremony. All spirits’ wishes and intentions are directed to a god called Ratalak. During the ritual, the Penan people will recite their prayers for protection, and prosperity and for their community to remain united. The findings of this study are derived from observations and interviews of the conduct of this ceremony. This ceremony was found to be in the form of animism and is adapted to the contemporary Christian elements. The person conducting the Pakan ceremony for the Penan animism group is called “Vaie Puwet” or Vaie Jau. Meanwhile, the people performing the ceremony amongst the Christian Penans are the religious leaders consisting of pastors, priests, and prayer leaders. Although this ceremony is animistic, it is still accepted by the community in the Christian way of worship that they currently adhere to.